Brexit, Archaeology and Heritage: Reflections and Agendas - Andrew Gardner; Rodney Harrison (Papers from the Institute of Archaeology, 2017)
This short report represents the closing comments to the forum covering Brexit, Archaeology and Heritage.
Keywords: Post-Truth; EU; Funding; Heritage; Brexit; Archaeology